Millennial Generation Communication Style of State Civil Apparatus; Performance Improvement and Work Quality - Wahyu Fattahulhidayat; Leonard Adrie Manafe; Sri Rahayu (Cita konsultindo, 2023)
This study aims to find out how the millennial generation's State Civil Apparatus (ASN) communication style is at the Office of Manpower and Transmigration of East Java Province (East Java Disnakertrans) by examining work culture aspects. The method used in conducting this research is using qualitative methods and post-positivism paradigm. Five research informants were taken as East Java Disnakertrans ASN employees. Data collection techniques were carried out using in-depth interviews with informants by including media recordings, videos, photos and notes as evidence of the results of conducting interviews in assisting the research process. The study results show that the communication style of the millennial generation ASN at the East Java Manpower Office is The Relinquishing Style due to their preference to collaborate with teams and deliberations so they could exchange thoughts, input or ideas with other team members. As well as wanting a conducive working atmosphere so every ASN could work more calmly and quickly. The millennial generation of ASN tends to prefer to hold discussions in order to gain insight, knowledge, or ideas that could add to their quality and performance. In addition, even though ASNs carry out work in a relaxed manner, ASNs are asked to be thorough in carrying out a job, so there are no mistakes in doing it even under pressure from superiors. in addition, ASNs are also more inclined to meet face-to-face when carrying out or completing a job because according to them face-to-face meetings are more effective than social media or other electronic mail. When ASNs are asked for their opinion or input, they tend not to beat around the bush thus their work gets done quickly.